Refined mapping of a gene for split hand-split foot malformation (SHFM3) on chromosome 10q25. Issue 12 (December 1996) - Raas-Rothschild, A; Manouvrier, S; Gonzales, M; Farriaux, J P; Lyonnet, S; Munnich, A
Abstract : Split hand-split foot malformation (SHFM) is a genetically heterogeneous limb developmental defect characterised by the absence of digital rays and syndactyly of the remaining digits. Three disease loci have recently been mapped to chromosomes 7q21 (SHFM1), Xq26 (SHFM2), and 10q25 respectively (SHFM3). We report the mapping of SHFM3 to chromosome 10q25 in two large SHFM families of French ancestry (Zmax for the combined families = 6.62 at theta = 0 for marker AFM249wc5 at locus D10S222). Two recombinant events reduced the critical region to a 9 cM interval (D10S1709-D10S1663) encompassing several candidate genes including a paired box gene PAX2 (Zmax = 5.35 at theta = 0). The fibroblast growth factor 8 (FGF 8), the retinol binding protein (RBP4), the zinc finger protein (ZNF32), and the homeobox genes HMX2 and HOX11 are also good candidates by both their position and their function.